SYNERGY OF COMMUNICATION AND OCCUPATIONAL HEALTH AND SAFETY: TRANSFORMATION OF EMPLOYEE PERFORMANCE AT PT LABELINDO MAS UTAMA NORTH JAKARTA - Sunarto, Ading; Nurlaili, Lili (International Journal of Multidisciplinary Research and Literature, 2024)
This study aims to determine the influence of Communication and Occupational Health Safety on Employee Performance at PT Labelindo Mas Utama North Jakarta. This research method uses a quantitative descriptive method. The sampling technique used was saturated sampling, which used a sample of 60 respondents. Data analysis uses validity tests, reality tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis tests. The result of this study is that the regression equation value Y = 5.248 + 0.382X1 + 0.496X2, and the correlation coefficient is 0.630, which means that the two variables have a strong relationship level. The value of determination or contribution of influence was 0.397 or 39.7%, while other factors influenced the remaining 60.3%. The hypothesis test obtained a t-value calculated > t table (18.768 > 3.16), which was also strengthened by the ρ value (0.000 < 0.05); thus, H0 was rejected, and H3 was accepted, meaning that there was a significant influence between Communication (X1) and Occupational Health Safety (X2) on Employee Performance (Y) at PT Labelindo Mas Utama